Flowcytometric Cytokine Profiling of T- Lymphocytes in Pediatric Aplastic Anemia - B, Aasha; Nangia, Anita; Sharma, Sunita; Chandra, Jagdish (Annals of Pathology and Laboratory Medicine, 2020)
Background: Aplastic anemia is a result of complex immune mediated marrow injury. As activated T cells play a pivotal role in immune response, study of cytokine profile in patients of aplastic anaemia (AA) will be of use in understanding the initiation and propagation of the disease. Methods: Thirty children with AA between ages 6 months to 18 years were included along with age & sex matched controls. Complete blood count (CBC) and bone marrow examination was done. They were grouped as Very severe aplastic anemia (VSAA), Severe aplastic anemia (SAA) and Non severe aplastic anemia (NSAA) as per standard guidelines. Intracytoplasmic expression of Type 1 cytokine (IFNÎ³) and Type 2 cytokine (IL4) was determined by Flow cytometry (FCM). CD8 and CD4 cell counts were also determined by FCM. Result: CD8 cell count was higher than the CD4 counts with reversal of CD4:CD8 ratio in all patients. Mean intracytoplasmic IFNÎ³ expression in CD8 and CD4 cells was higher in cases than in controls (p<0.0001) and showed graded positive correlation with the severity of the disease (p<0.0001). Type 2 cytokine (IL4) did not show any such correlation. Conclusion: IFN gamma expression in T cells can be useful in predicting severity of the disease and also response to immunosuppression.